ALTERNATIVE PROFIT-SHARING SYSTEM IN THE MUDHARABA SCHEME IN SHARIA BANKING PERSPECTIVE M. BAQIR AL-SADR - Muhammad, Adib; Rosyad, Sabilal; Fakhrina, Agus; Muhtarom, Ali (Jurnal Ekonomi dan Bisnis, 2024)
The profit-sharing system with a mudharaba scheme is an early concept of Islamic banking. However, mudharaba is starting to be abandoned by customers and sharia banks because it carries high risks. This research will discuss Muhammad Baqir al-Sadr's thoughts on the profit-sharing system in the mudharaba scheme. The method used is descriptive qualitative by taking primary data sources in the form of a book written directly by al-Sadr entitled: Al-Bank al-Laribawi fi al-Islam. This research found several results, namely: (1) the profit-sharing system in al-Sadr's version of the mudharaba scheme is different from the mudharaba concept in general. This research further shows al-Sadr's prominence in the field of sharia economics, because al-Sadr also has an original concept about Islamic banking. (2) This research found that al-Sadr's thoughts have significance for efforts to develop sharia banking in the future, especially regarding strengthening moral values in the relationship between sharia banks and customers. (3) This research further shows al-Sadr's prominence in the field of sharia economics, because al-Sadr also has an original concept about Islamic banking.